Three-step method for menstrual and oral contraceptive cycle verification - Schaumberg, M.; Jenkins, D.; Janse de Jonge, X.; Emmerton, Lynne; Skinner, T. (Elsevier Australia, 2016)
Objectives: Fluctuating endogenous and exogenous ovarian hormones may influence exercise parameters; yet control and verification of ovarian hormone status is rarely reported and limits current exercise science and sports medicine research. The purpose of this study was to determine the effectiveness of an individualised three-step method in identifying the mid-luteal or high hormone phase in endogenous and exogenous hormone cycles in recreationally-active women and determine hormone and demographic characteristics associated with unsuccessful classification. Design: Cross-sectional study design. Methods: Fifty-four recreationally-active women who were either long-term oral contraceptive users (n = 28) or experiencing regular natural menstrual cycles (n = 26) completed step-wise menstrual mapping, urinary ovulation prediction testing and venous blood sampling for serum/plasma hormone analysis on two days, 6-12. days after positive ovulation prediction to verify ovarian hormone concentrations. Results: Mid-luteal phase was successfully verified in 100% of oral contraceptive users, and 70% of naturally-menstruating women. Thirty percent of participants were classified as luteal phase deficient; when excluded, the success of the method was 89%. Lower age, body fat and longer menstrual cycles were significantly associated with luteal phase deficiency. Conclusions: A step-wise method including menstrual cycle mapping, urinary ovulation prediction and serum/plasma hormone measurement was effective at verifying ovarian hormone status. Additional consideration of age, body fat and cycle length enhanced identification of luteal phase deficiency in physically-active women. These findings enable the development of stricter exclusion criteria for female participants in research studies and minimise the influence of ovarian hormone variations within sports and exercise science and medicine research.